PELATIHAN MEMBUAT VPN MENGGUNAKAN LAYANAN CLOUD COMPUTING SMK MA’ARIF NU 1 KEMBARAN, BANYUMAS - Priyanto, Agus; Adam, Ipam Fuadina (Dharma: Jurnal Pengabdian Masyarakat, 2021)
Cloud computing is a technology that has powerful computing resources that can be applied to many organizations by using dynamic scalability as a virtual service source via the internet. SMK Ma'arif NU 1 Kembaran has a 2013 TKJ curriculum. The curriculum has topics such as Computer Assembly, Network Operating Systems and Server Administration. In the subject of Network Operating Systems, there is no subject that discusses cloud computing technology. This technology will have an impact on the average score of students before training to make VPN with cloud computing, namely 83, 12 and after training to 89.06 so that there is a descriptive increase. The hypothesis used is a two-way hypothesis so that it uses two tails with the result t table that is 2.039513 with a p value of 0.01249. Because the p value is smaller than alpha 5% or by looking at the value | t count | > t table then Ho is rejected. This means that there is a significant difference in the level of understanding of students before and after training to make VPN with cloud computing.Cloud computing is a technology that has powerful computing resources that can be applied to many organizations by using dynamic scalability as a virtual service source via the internet. SMK Ma'arif NU 1 Kembaran has a 2013 TKJ curriculum. The curriculum has topics such as Computer Assembly, Network Operating Systems and Server Administration. In the subject of Network Operating Systems, there is no subject that discusses cloud computing technology. This technology will have an impact on the average score of students before training to make VPN with cloud computing, namely 83, 12 and after training to 89.06 so that there is a descriptive increase. The hypothesis used is a two-way hypothesis so that it uses two tails with the result t table that is 2.039513 with a p value of 0.01249. Because the p value is smaller than alpha 5% or by looking at the value | t count | > t table then Ho is rejected. This means that there is a significant difference in the level of understanding of students before and after training to make VPN with cloud computing.